Metaheuristic approaches to portfolio optimization - Ray, Jhuma, 1980- (Business Science Reference, 2019)
"This book explores the aspects of industrial portfolio management with reference to proper selection of financial instruments in a financial portfolio management scenario from a metaheuristic approach. It also illustrates the common measures used for the evaluation of risks/returns of portfolios in real life situations"--